PENGARUH PEMBIAYAAN MIKRO SYARIAH TERHADAP TINGKAT PERKEMBANGAN USAHA MIKRO KECIL MENENGAH (UMKM) PADA ANGGOTA BMT DI JAWA BARAT - Uus Ahmad Husaeni; Tini Kusmayati Dewi (BJRM (Bongaya Journal of Research in Management), 2019)
This study aims to analyze the role of Islamic microfinance on the level of development of small and medium micro enterprises in BMT members in West Java. The research method is carried out using a type of quantitative associative approach. The population of this study are members of BMT Baytul Ikhtiar Bogor, BMT ItQan Bandung, BMT Amanah Bersama Bandung and BMT Ibadurrahman Sukabumi, which number 40 people. While the technique for analyzing data is using Simple Linear Regression analysis. The results of the study found that the role of Islamic microfinance in providing business capital to members of BMT has an important role to improve small and medium micro enterprises. The R-Square value is 0.529 or 52.90%. It is seen that the independent variable of Islamic microfinance in explaining the dependent variable of SMEs Business Development Levels on BMT members is 52.90%, the remaining 47.10% is explained by other variables outside the model that are not examined. Based on the results of testing the F test, the value of Fcount> Ftable is 61.875 > 3.24 with the hypothesis H0 being rejected and Ha being accepted with a significance of 0.000 < 0.05.